Under-expression of ?8 integrin aggravates experimental atherosclerosis - Menendez-Castro, Carlos; Cordasic, Nada; Neureiter, Daniel; Amann, Kerstin Ute; Marek, Ines; Volkert, Gudrun; Stintzing, Sebastian; Jahn, Angelika; Rascher, Wolfgang; Hilgers, Karl Friedrich; Hartner, Andrea (Journal of Pathology, 2015)
Integrins play an important role in vascular biology. The ?8 integrin chain attenuates smooth muscle cell migration but its functional role in the development of atherosclerosis is unclear. Therefore, we studied the contribution of ?8 integrin to atherosclerosis and vascular remodelling. We hypothesized that ?8 integrin expression is reduced in atherosclerotic lesions, and that its under-expression leads to a more severe course of atherosclerosis. ?8 Integrin was detected by immunohistochemistry and qPCR and ?8 integrin-deficient mice were used to induce two models of atherosclerotic lesions. First, ligation of the carotid artery led to medial thickening and neointima formation, which was quantified in carotid cross-sections. Second, after crossing into ApoE-deficient mice, the formation of advanced vascular lesions with atherosclerotic plaques was quantified in aortic en face preparations stained with Sudan IV. Parameters of renal physiology and histopathology were assessed: ?8 integrin was detected in the media of human and murine vascular tissue and was down-regulated in arteries with advanced atherosclerotic lesions. In ?8 integrin-deficient mice (?8(-/-) ) as well as ?8(+/-) and ?8(+/+) littermates, carotid artery ligation increased media:lumen ratios in all genotypes, with higher values in ligated ?8(-/-) and ?8(+/-) compared to ligated ?8(+/+) animals. Carotid artery ligation increased smooth muscle cell number in the media of ?8(+/+) mice and, more prominently, of ?8(-/-) or ?8(+/-) mice. On an ApoE(-/-) background, ?8(+/-) and ?8(-/-) mice developed more atherosclerotic plaques than ?8(+/+) mice. ?8 Integrin expression was reduced in ?8(+/-) animals. Renal damage with increased serum creatinine and glomerulosclerosis was detected in ?8(-/-) mice only. Thus, under-expression of ?8 integrin aggravates vascular lesions, while a complete loss of ?8 integrin results in reduced renal mass and additional renal disease in the presence of generalized atherosclerosis. Our data support the hypothesis that integrin ?8?1 has a protective role in arterial remodelling and atherosclerosis. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
EVALuna2:3752